Calibration on co-located ad-hoc multi mobile system - Teo, Rhun Ming; Ong, Beng Liang; Mohd Norowi, Noris; Mansor, Evi Indriasari; Dey, Prasenjit; Jamil, Izdihar (Association for Computing Machinery, 2016)
This paper presents findings about connectivity issues when using clock wise swipe gesture of mobiTop system. The mobiTop system is a multi-mobile system that allows users to come together at any location and perform collaborative tasks and information sharing by extending their mobile devices. This study investigates the user experience issues when multiple users calibrate and align multiple mobile devices using the mobiTop system. From the study, users took an average of 5.47 minutes to initiate connections between multiple devices. The finding shows that the existing calibration setting is too complicated for the users despite the step-by-step tutorial provided by the system. The findings also show that although only one user is needed to initiate to connectivity, most of the users tend to contribute towards simultaneous connectivity input leading to system disorientation. Following this, several connectivity methods explored that can be employed by the mobiTop system to minimize connectivity time and promote a seamless integration between the users and the system.